FEATURES OF INTRODUCTORY CONSTRUCTION FUNCTIONING IN SENTENCE STRUCTURE - Svetlana N. Mihaleva; Irina N. Kostina (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The study is devoted to the problem of semantic features of introductory constructions (hereinafter referred to as IC). Currently, we are considering the synthesis of the main and introductory sentences with a single complex syntactic construction, in which the introductory sentence is semantically and grammatically connected to the main sentence as an organizing center. Since introductory constructions have additional semantic features and are sometimes able to influence with their help the general meaning of a newly formed utterance, it seems appropriate to consider their functions and the reasons for their use by the author of the utterance.